Sub-Surface Carbon Stocks in Northern Taiga Landscapes Exposed in the Batagay Megaslump, Yana Upland, Yakutia - Andrei G. Shepelev; Alexander Kizyakov; Sebastian Wetterich; Alexandra Cherepanova; Alexander Fedorov; Igor Syromyatnikov; Grigoriy Savvinov (Land, 2020)
The most massive and fast-eroding thaw slump of the Northern Hemisphere located in the Yana Uplands of Northern Yakutia was investigated to assess in detail the cryogenic inventory and carbon pools of two distinctive Ice Complex stratigraphic units and the uppermost cover deposits. Differentiating into modern and Holocene near-surface layers (active layer and shielding layer), highest total carbon contents were found in the active layer (18.72 kg m−2), while the shielding layer yielded a much lower carbon content of 1.81 kg m−2. The late Pleistocene upper Ice Complex contained 10.34 kg m−2 total carbon, and the mid-Pleistocene lower Ice Complex 17.66 kg m−2. The proportion of organic carbon from total carbon content is well above 70% in all studied units with 94% in the active layer, 73% in the shielding layer, 83% in the upper Ice Complex and 79% in the lower Ice Complex. Inorganic carbon is low in the overall structure of the deposits.